2002
DOI: 10.1038/sj.bjp.0704667
|View full text |Cite
|
Sign up to set email alerts
|

Receptor subtypes Y1 and Y5 mediate neuropeptide Y induced feeding in the guinea‐pig

Abstract: 1 Neuropeptide Y (NPY) is one of the most potent stimulants of food intake. It has been debated which receptor subtype mediates this response. Initially Y 1 was proposed, but later Y 5 was announced as a`feeding' receptor in rats and mice. Very little is known regarding other mammals. The present study attempts to characterize the role of NPY in feeding behaviour in the distantly related guinea-pig. When infused intracerebroventricularly, NPY dose-dependently increased food intake. 2 PYY, (Leu 31 ,Pro 34 )NPY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 60 publications
3
41
0
Order By: Relevance
“…125 I]PYY binding studies indicated that this construct displayed high affinities for the agonist PYY and the nonpeptide Y1 antagonist BIBO3304 (Wieland et al, 1998;Lecklin et al, 2002) (Table 1), equivalent to those we have previously reported for native and fluorescent protein-modified Y1 receptors (Kilpatrick et al, 2010(Kilpatrick et al, , 2012, and an estimated [ (Table 1) (Kilpatrick et al, 2010). Automated confocal imaging studies (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…125 I]PYY binding studies indicated that this construct displayed high affinities for the agonist PYY and the nonpeptide Y1 antagonist BIBO3304 (Wieland et al, 1998;Lecklin et al, 2002) (Table 1), equivalent to those we have previously reported for native and fluorescent protein-modified Y1 receptors (Kilpatrick et al, 2010(Kilpatrick et al, , 2012, and an estimated [ (Table 1) (Kilpatrick et al, 2010). Automated confocal imaging studies (Fig.…”
Section: Resultssupporting
confidence: 79%
“…NPY is a widely expressed central nervous system modulator, noted for its role in appetite regulation when released from hypothalamic arcuate neurons (Michel et al, 1998;Brothers and Wahlestedt, 2010). Orexigenic effects of NPY are mediated through a combination of Y1 and Y5 receptor subtypes coexpressed in paraventricular target cells (Gerald et al, 1996;Cabrele et al, 2000;Lecklin et al, 2002;Brothers and Wahlestedt, 2010). Y1 antagonists [e.g., (R)-N 2 -(diphenylacetyl)-N-[(4-(aminocarbonylaminomethyl)phenyl) methyl]-argininamide (BIBO3304); Wieland et al, 1998] and Y5 antagonists [e.g., N-[[trans-4-[[(4-amino-2-quinazolinyl) amino]methyl]cyclohexyl]methyl]-1-naphthalene sulfonamide hydrochloride (CGP71683); Criscione et al, 1998] were explored for their abilities to inhibit appetite.…”
Section: Introductionmentioning
confidence: 99%
“…However, the anorectic effect of PYY seems to be mediated by by PYY (3-36), but not by PYY ). This appears to be due to the specific affinity of the dominating peptide PYY(3-36) for the Y2 receptor, and due to the fact that the Y1 and Y5 receptors are associated with increased feeding behavior [75].…”
Section: Peptide Yymentioning
confidence: 99%
“…All members are C-terminally amidated polypeptides consisting of 36 amino acids (1) and are involved in multiple physiological processes, including memory retention (2, 3), feeding behavior (4,5), control of blood pressure (6,7), and seizure (8).…”
mentioning
confidence: 99%
“…Y 1 R and Y 4 R require the complete N terminus of the ligand (15,19,20). Y 5 R accepts peptides with the deletion of the first amino acid (21), and Y 2 R even binds significantly shorter peptides (NPY ) or centrally truncated analogs ([Ahx [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ]NPY) with only minor effects on affinity (19,22). However, the C-terminal pentapeptide of all natural ligands was identified as an essential region for binding to all YRs (23,24), and these residues of the ligand C terminus seem to represent a core contact domain.…”
mentioning
confidence: 99%